Abnormal Laboratory Results - Edited by Kellerman, Geoffrey (Sydney McGraw-Hill, 2006)
Contains a collection of common abnormal test results which examine the dilemmas of abnormal tests. This work analyses and interprets each text in a structured, logical way and assesses it in terms of its abnormal and normal reference range. It presents the results in clinical contexts for accurate prognosis and recommendations on management.
Include Index
Keywords: Diagnosis, Laboratory--Evaluation -- Clinical chemistry -- Diagnostic errors